The Idea of an Old Quran Manuscript: On the Commercialization of the Indonesian Islamic Heritage - Wieringa, Edwin (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
A Qurâan manuscript, now in the possession of the University of Cologne, Germany (call number Cod. Malaiologie 001/2012), can be regarded as a âfakeâ in the sense of having a misleading appearance. This manuscript is a fairly recent bricolage which aims to represent the idea of an old Qurâan manuscript, thereby catering to the increased demand on the international market for old manuscripts from insular Southeast Asia.